Clinical evaluation techniques for injury risk assessment in elite swimmers: A systematic review - Schlueter, K. R.; Pintar, J. A.; Wayman, K. J.; Hartel, L. J.; Briggs, M. S. (Sports Health: A Multidisciplinary Approach, 2021)
Context: Evidence concerning a systematic, comprehensive injury risk assessment in the elite swimming population is scarce. Objective: To evaluate the quality of current literature regarding clinical assessment techniques used to evaluate the presence and/or development of pain/injury in elite swimmers and to categorize objective clinical assessment tools into relevant predictors (constructs) that should consistently be evaluated in injury risk screens of elite swimmers. Data Sources: PubMed, Embase, Scopus, CINAHL, SPORTDiscus, PEDro, and the Cochrane Library Reviews were searched through September 2018. Study Selection: Studies were included for review if they assessed a correlation between clinic-based objective measures and the presence and/or development of acute or chronic pain/injury in elite swimmers. All body regions were included. Elite swimmers were defined as National Collegiate Athletic Association, collegiate, and junior-, senior-, or national-level swimmers. Only cohort and cross-sectional studies were included (both prospective and retrospective); randomized controlled trials, expert opinion, and case reports were excluded, along with studies that focused on interventions, performance, or specific swim-stroke equipment or technology. Study Design: Systematic review and qualitative analysis. Level of Evidence: Level 3. Data Extraction: PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were utilized at each phase of review by 2 reviewers; a third reviewer was utilized for tie breaking purposes. Qualitative analysis was performed using the Methodological Items for Non-Randomized Studies (MINORS) assessment tool. Results: A total of 21 studies assessed the presence and/or development of injury/pain in 3 different body regions: upper extremity, lower extremity, and spine. Calculated average MINORS scores for comparative (n = 17) and noncomparative (n = 4) studies were 18.1 of 24 and 10.5 of 16, respectively. Modifiable, objectively measurable injury risk factors in elite swimmers were categorized into 4 constructs: (1) strength/endurance, (2) mobility, (3) static/dynamic posture, and (4) patient-report regardless of body region. Conclusion: Limited evidence exists to draw specific correlations between identified clinical objective measures and the development of pain and/or injury in elite swimmers.